Bezpieczeństwo energetyczne w dokumentach strategicznych Unii Europejskiej i Federacji Rosyjskiej – problemy definicyjne oraz próba ich przezwyciężenia (Politeja, 2016)
Energy security in the EU’s and Russia’s strategic documents – how to overcome conceptual problemsAnalyzing EU-Russia relations one may find significant difference regarding the energy security definition. From the Russian perspective this concept is defined mainly through the technical prism focusing on stable and secure supply. In turn, many European researchers add economic and environmental dimensions of this concept underlying the role of competitive market and interrelations with climate issue. In this paper author tries to reduce a difference between these two positions. He aims at elaborating broad definition of the energy security which should help for better analysis EU-Russia energy relations. He states that existing definition based on three abovementioned elements like security of supply, free market, and sustainable development, is incomplete and should therefore be extended by the fourth component, so called social and political agreement.